ZnO@ZIF-8 core–shell heterostructures with improved photocatalytic activity. Issue 24 (2nd June 2021) - Chen, Mei-Hua; Lu, Qian-Ying; Li, Yi-Ming; Chu, Ming-Ming; Cao, Xue-Bo
Abstract : ZnO@ZIF-8 heterostructures with ZnO as the core and ZIF-8 as the shell were successfully fabricated and completely degraded methylene blue in ∼4.5 min under solar light irradiation. Abstract : ZnO semiconductors have been widely used as photocatalysts. However, the weak photodegradation under solar light restrains their further application. In this study, porous zeolitic imidazolate framework-8 (ZIF-8), which has a high specific surface, was combined with ZnO nanorods to fabricate ZnO@ZIF-8 core–shell heterostructures, with the ZnO nanorods and ZIF-8 as the core and the shell, respectively. Scanning electron microscopy and transmission electron microscopy measurements revealed that the ZnO nanorods were wrapped by a ZIF-8 shell. The pore size distribution of these ZnO@ZIF-8 nanocomposites included micropores, mesopores, and macropores. Moreover, a Brunauer–Emmett–Teller analysis showed an increase compared with the ZnO nanorods in the overall specific surface area. Due to a synergistic effect of ZnO and ZIF-8, the as-synthesized ZnO@ZIF-8 heterostructures exhibited high photocatalytic activity and completely degraded methylene blue in ∼4.5 min under solar light irradiation. Furthermore, stability experiments proved that the as-prepared ZnO@ZIF-8 nanocomposites retain over 95% of their photocatalytic activity after four cycles.